Prevalence and disease associations in feline thrombocytopenia: a retrospective study of 194 cases. (22nd January 2018) - Ellis, J.; Bell, R.; Barnes, D.C.; Miller, R.
Abstract : Objectives: To assess the prevalence of thrombocytopenia in a referral population of cats in the UK, to identify disease processes associated with thrombocytopenia and to assess the proportion of thrombocytopenic cats that tested positive for feline leukaemia virus or feline immunodeficiency virus. Materials and Methods: Retrospective analysis of medical records at a UK referral hospital. Cats were grouped by mechanism of thrombocytopenia and disease process (where known). Results: Prevalence of thrombocytopenia was 5·9%. The most common disease processes associated with thrombocytopenia were haematological or infectious disease and neoplasia; 11% of thrombocytopenic cats tested were positive for feline leukaemia virus, which is lower than reported previously. Cats presenting with unexplained haemorrhage had significantly lower platelet counts than other thrombocytopenic cats. Primary immune‐mediated thrombocytopenia was less commonly diagnosed than in dogs and associated with the most severe platelet depletion in this study. Clinical Significance: Thrombocytopenia in cats may be more prevalent than previously reported and severe thrombocytopenia may be associated with spontaneous haemorrhage. Severe thrombocytopenia in cats appears less commonly immune‐mediated than in dogs. Thrombocytopenia did not appear to be associated with retroviral infections.